EFEKTIVITAS PEMBERDAYAAN PEREMPUAN TERHADAP KEBERHASILAN PROGRAM KEUARGA BERENCANA DI DESA MUARA KAMAN ULU TAHUN 2023 - Susi Julianti; Dwi Prihatin Era; Ega Ersya Urnia; Endah Wahyuni (ITKM WIDYA CIPTA HUSADA, 2023)
Family planning is a government program that aims to regulate child birth, reduce child mortality, improve maternal welfare, quality of health services and community nutrition. Family planning programs can be implemented through health promotion using the media because the media can assist in conveying information and can reduce misunderstandings. The aim of this study is to find out the effectiveness of women's empowerment on the success of the family planning program for couples of childbearing with lower middle income in Muara Kaman Ulu Village, Muara Kaman District in 2023. This type of research is pre-experimental with one group pretest-posttest. The population in this study were all couples of childbearing with middle to lower income in Muara Kaman Ulu Kaman Village, a total of 101 people, while a sample of 41 respondents was taken using a purposive sampling technique. The data analysis technique uses the Wilcoxon test. There is an influence of Women's Empowerment on the Success of the Family Planning Program for couples of childbearing who have middle to lower incomes in Muara Kaman Ulu Village, Muara Kaman District in 2023. Women's empowerment is a strategy to increase women's access to family planning in order to increase the interest of couples of childbearing to participate in family planning and increasing the knowledge of couples of childbearing regarding family planning. Empowerment of women has an influence on the interest of couples of childbearing in using family planning and affects the level of knowledge of couples of childbearing regarding family planning